The reflection of sri lankan sensibility in lakdasa wikkramasinha’s poetry - Paramanathan, L. (University of Jaffna, 2012)
Lakdasa Wikkramasinha, the young Sri Lankan poet who died by drowning in 1978, has been considered as the most ‘original’ poet appeared on the Sri Lankan scene. His poetry is very much related to Sri Lankan lifestyle, culture and society. There is a local inspiration that governs most of his poems. Furthermore, his language is peppered with local forms and idioms which according to most critics, certainly reveals the sense of ‘Sri Lankanness’. There are also elements of post-colonial hybridity and bi culturalism in his poetry. This paper looks into the possible ways by which we can attribute the notion of ‘originality’ to Lakdasa Wikkramasinha’s poetry. The paper examines in a detailed way, how Wikkramasinha tries to capture the Sri Lankan experience in his poetry and the emergence of Sri Lankan identity through the usage of his language, which is considered as distinctively ‘Sri Lankan’.
Keywords: Biculturalism; Originality; Post colonial hybridity; Sri lankanness